2023
DOI: 10.1186/s12913-023-09028-z
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions of sexually transmitted and blood borne infections testing services during the COVID-19 pandemic: accounts of service providers in Ontario, Canada

Abstract: Background Since the onset of the COVID-19 pandemic in March 2020 in Canada, the availability of sexual health services including sexually transmitted and blood-borne infection (STBBI) testing has been negatively impacted in the province of Ontario due to their designation as “non-essential” health services. As a result, many individuals wanting to access sexual healthcare continued to have unmet sexual health needs throughout the pandemic. In response to this, sexual health service providers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies in Australia found reduced STI consultations before lockdown compared to during lockdown [73] a move toward telehealth for testing services [62,74]. Similarly, sexual health providers in Canada emphasised severe reductions in the availability of sexually transmitted and blood-borne infection testing due to government deployment of staff toward the COVID-19 response; thus, some clinics closed or adopted fewer hours [75]. This study reported the adoption of two models of care: 1) a "quick clinic" for asymptomatic patients to self-test for gonorrhoea and chlamydia at the clinic, but not for tests that require blood (e.g., HIV); and 2) a virtual clinic which replaced most in-person testing services, with few exceptions for high-risk clients; virtual clinics were seen as largely acceptable across participants [75].…”
Section: Sexual Health Servicesmentioning
confidence: 99%
“…Studies in Australia found reduced STI consultations before lockdown compared to during lockdown [73] a move toward telehealth for testing services [62,74]. Similarly, sexual health providers in Canada emphasised severe reductions in the availability of sexually transmitted and blood-borne infection testing due to government deployment of staff toward the COVID-19 response; thus, some clinics closed or adopted fewer hours [75]. This study reported the adoption of two models of care: 1) a "quick clinic" for asymptomatic patients to self-test for gonorrhoea and chlamydia at the clinic, but not for tests that require blood (e.g., HIV); and 2) a virtual clinic which replaced most in-person testing services, with few exceptions for high-risk clients; virtual clinics were seen as largely acceptable across participants [75].…”
Section: Sexual Health Servicesmentioning
confidence: 99%
“…Although some qualitative studies have been conducted exploring the experiences of virtual care during COVID‐19 from the perspective of health‐care providers (Downing et al., 2021; James et al., 2021; Van Citters et al., 2021; Zhao et al., 2021), only a few studies have adequately described the experiences of service users (Baraitser & Lupton, 2023; Triantafillou et al., 2021; Vilendrer et al., 2022). There is also limited scholarship exploring the virtual care experiences of gay, bisexual and queer men (GBQM) during COVID‐19 in Canada (Gilbert et al., 2022; Ryu et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential effect of the COVID-19 pandemic could be the closure of important sexual and reproductive health centers: staff and public resources had to be reallocated to tackle the pandemic, leaving “non-essential” services neglected [ 23 ]. The temporary closure of some sexual health services, due to their designation as “non-essential”, negatively impacted the patients, some of whom had unmet sexual health needs for the duration of the stricter measure of lockdown.…”
Section: Introductionmentioning
confidence: 99%